Effects of anti-inflammatory drugs on distinct endotypes of chronic rhinosinusitis without nasal polyps: comparison using an ex-vivo model - Pesold, Vanessa-Vivien; Wendler, O.; Mueller, S. K. (European Review for Medical and Pharmacological Sciences, 2024)
OBJECTIVE: The objectives of this study were to characterize the endotypes of different chronic rhinosinusitis without nasal polyps (CRSsNP) samples, to investigate the effects of certain anti-inflammatory drugs on these endotypes, and to investigate the effect of the same drugs on recently identified CRSsNP marker proteins. PATIENTS AND METHODS: Initially, ethmoid tissues (ETs) from CRSsNP patients (n=12) were dissected into sections and incubated with the addition of mometasone, verapamil, cenicriviroc, and dupilumab. Cell culture media were collected after 24 hours, and the contents of the secreted proteins interferon-gamma (IFN-γ), interleukin (IL)-5, IL-17A, macrophage inflammatory protein-1 beta (MIP-1β), resistin and platelet (P)-selectin were measured using enzyme-linked immunosorbent assay (ELISA). The endotypes were characterized using the unstimulated samples. The fold changes of protein secretion caused by the analyzed substances were calculated. For each protein, the samples of the distinct endotypes were compared with the remaining samples. RESULTS: Both single and mixed endotypes were identified within the CRSsNP samples, whereas none of the typical endotype-defining cytokines were elevated in a significant portion of the samples. All of the incubated medicaments greatly reduced the tissue secretions of IFN-γ and IL-5 in type 1 CRS while causing a lower secretion of IL-17A in all endotypes compared to the remaining samples. Among the analyzed CRSsNP marker proteins, the distinct endotypes revealed different reactions to the drugs. Dupilumab induced more effects among the examined cytokines than the marker proteins but did not stand out from the other substances overall. CONCLUSIONS: Medications used to treat CRS may have different effects on distinct CRS endotypes.
CRIS-Team Scopus Importer:2024-11-15